An integrated approach for increasing breeding efficiency in apple and peach in Europe. Issue 1 (1st March 2018) - Laurens, Francois; Aranzana, Maria José; Arus, Pere; Bassi, Daniele; Bink, Marco; Bonany, Joan; Caprera, Andrea; Corelli-Grappadelli, Luca; Costes, Evelyne; Durel, Charles-Eric; Mauroux, Jehan-Baptiste; Muranty, Hélène; et al.
Abstract: Despite the availability of whole genome sequences of apple and peach, there has been a considerable gap between genomics and breeding. To bridge the gap, the European Union funded the FruitBreedomics project (March 2011 to August 2015) involving 28 research institutes and private companies. Three complementary approaches were pursued: (i) tool and software development, (ii) deciphering genetic control of main horticultural traits taking into account allelic diversity and (iii) developing plant materials, tools and methodologies for breeders. Decisive breakthroughs were made including the making available of ready-to-go DNA diagnostic tests for Marker Assisted Breeding, development of new, dense SNP arrays in apple and peach, new phenotypic methods for some complex traits, software for gene/QTL discovery on breeding germplasm via Pedigree Based Analysis (PBA). This resulted in the discovery of highly predictive molecular markers for traits of horticultural interest via PBA and via Genome Wide Association Studies (GWAS) on several European genebank collections. FruitBreedomics also developed pre-breeding plant materials in which multiple sources of resistance were pyramided and software that can support breeders in their selection activities. Through FruitBreedomics, significant progresses were made in the field of apple and peach breeding, genetics, genomics and bioinformatics of which advantage will be made by breeders, germplasm curators and scientists. A major part of the data collected during the project has been stored in the FruitBreedomics database and has been made available to the public. This review covers the scientific discoveries made in this major endeavour, and perspective in the apple and peach breeding and genomics in Europe and beyond. Genomics: New resources for apple and pear breeding: A Europe-led effort to bridge the gap between genomics and breeding offers a new resource to support apple and peach production. A team led by François Laurens from the Research Institute in Horticulture and Seeds (IRHS) in Angers, France, review the tools, methodologies and scientific discoveries made through FruitBreedomics, a project that ran between 2011 and 2015 and involved 28 different research and private companies from around the world. These new molecular and bioinformatics tools include DNA arrays for mapping genetic diversity, computer software for analyzing genetic information and novel methods for understanding commercially important traits such as fruit quality and resistance to stresses. The project's materials should help apple and peach producers better plan their breeding programs so as to meet grower and consumer demand for high-quality fruit with desired characteristics.